Smiling again after fifteen years of torture - Musaniwabo, Charline (Torture Journal, 2018)
I am Charline Musaniwabo. I was born in 1976. My parents were farmers. I lived with them up to April 1994. My life completely changed during the genocide, having been married forcibly and losing many of my family members. I was born into a family of nine children, four boys and five girls. Five siblings and both my parents died during the genocide. Four of us escaped. I did not get a chance to marry a man I loved, because I was taken by force in 1994 by a neighbour who raped and married me. I live with the three children I conceived with this man.